2012
DOI: 10.1007/s00221-012-3227-0
|View full text |Cite
|
Sign up to set email alerts
|

Muscle agonist–antagonist interactions in an experimental joint model

Abstract: The experiments presented here and performed in anaesthetized cats aimed at studying the dynamics of interactions between antagonist muscle groups. The tendons of triceps surae muscles of both hindlimbs were connected with an artificial joint (a pulley installed on a shaft). The muscles were activated by the distributed stimulation of five filaments of cut ventral roots L7–S1 on both sides of the spinal cord; movements were evoked by the rate-modulation of the stimulation trains. The study mostly compared prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…In particular, we carried out the corresponding study on a model of interaction of antagonist muscles; an "artificial joint" was used in these experiments. As was found, different modes of activation of the antagonist muscles significantly affect the hysteresis manifestations in the course of changes of the angles in the artificial joint [2]. This allowed us to believe that the CNS, when selecting the strategy of control of one movement or another, should take into account the existence of hysteresis in the course of formation of motor commands, and the respective regularities can be rather complicated.…”
Section: Discussionmentioning
confidence: 82%
“…In particular, we carried out the corresponding study on a model of interaction of antagonist muscles; an "artificial joint" was used in these experiments. As was found, different modes of activation of the antagonist muscles significantly affect the hysteresis manifestations in the course of changes of the angles in the artificial joint [2]. This allowed us to believe that the CNS, when selecting the strategy of control of one movement or another, should take into account the existence of hysteresis in the course of formation of motor commands, and the respective regularities can be rather complicated.…”
Section: Discussionmentioning
confidence: 82%
“…The movement phases are primarily accompanied by co-contractions of the antagonistic muscles within the areas adjacent to the zones of their direct loading. The co-contraction patterns can distinctly reduce both the after-effects of the ongoing residual movements at the apexes of movement and the uncertainty effects related to muscle hysteresis [13,17]. Behavioral studies of postural tasks have demonstrated that subjects use muscle co-contraction as a strategy of stabilization of the limb joints in the presence of external loadings [18].…”
Section: Discussionmentioning
confidence: 99%
“…The movement phases are primarily accompanied by antagonist co-contractions, whereas the steady-states are connected with a preferential use of reciprocal activation. Recently, the movement dynamic under these basic patterns of the antagonist activations was studied via the experimental model of two antagonistic muscles (Gorkovenko et al, 2012 ). It has been demonstrated that a reciprocal activation pattern can essentially linearise the movements after a change in their direction, providing they also exhibit a fast beginning; the co-contraction patterns can distinctly reduce the undesirable hysteresis after-effects, such as the ongoing residual movements at the apexes of activity.…”
Section: Discussionmentioning
confidence: 99%